Canon EOS 60D for dummies - King, Julie Adair (John Wiley & Sons, 2011)
If you own a Canon 60D, you?ve got a camera for advanced amateurs and one that?s very close to professional-level equipment. Now it?s time to make sure you get the very most out of all that power. Julie Adair King teams up with Robert Correll to help digital camera users catch their skills up to what their cameras have to offer in this fun but thorough guide. Understand all your camera?s features, move beyond the security blanket of Auto mode, and start capturing the pictures you?ve dreamed of.